Characteristics of Hypertension Patients at Lanto Dg Pasewang Jeneponto Regional General Hospital 2022-2023 - Saputra, Muh Farhan; Royani, Ida; Hamzah, Pratiwi Nasir; Harahap, Muhammad Wirawan; Tahir, Akina Maulidhany (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Cardiovascular diseases, including hypertension (blood pressure >/140/90 mmHg), contribute to heart and vascular damage. Risk factors include non-modifiable factors (age, gender, family history) and modifiable factors (smoking, behavior, alcohol). Objective: This study aimed to identify the characteristics and risk factors of hypertensive patients at RSUD Lanto DG Pasewang Jeneponto. Methods: A descriptive study using secondary data from medical records of hypertensive patients at RSUD Lanto DG Pasewang Jeneponto was conducted in September 2024. Data were analyzed descriptively by age, gender, hypertension grade, body mass index (BMI), and comorbidities. Results: A total of 93 patients were included. Most patients were aged 61–70 years (31.2%), followed by 51–60 years (26.9%). Females (59.1%) were more affected than males (40.9%). The majority (92.5%) had grade 2 hypertension. Based on BMI, 63.4% were normal, 21.5% overweight, and the rest underweight, obese, or grade 2 obese. Comorbidities included heart disease (76.3%), diabetes (14%), and kidney failure (9.7%). Conclusion: Most hypertensive patients at RSUD Lanto DG Pasewang Jeneponto were aged 60–70 years, female, had normal nutritional status, grade 2 hypertension, and a history of heart disease.